PENERAPAN DIVERSI PENYELESAIAN ALTERNATIF PERKARA ANAK DI KEPOLISIAN RESOR KOTA PEKANBARU BERDASARKANUNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Nidya, Dea; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Child is someone who is not yet eighteen years old, including child who is still in the womb. In the case of children who has problems in the law is known by a way of diversion. Diversion istransfering problems of a child from the settlement of the criminal justice process to the outside of the criminal justice process. It is stipulated in Article 1 paragraph (7) of Law Number 11 Year 2012 on Child Criminal Justice System. The research objective of this minithesis, among others; First, to determine implementation of diversion Pekanbaru City Police, Second, To know the barriers that are faced Pekanbaru City Police, Third, To know the efforts of City Police Pekanbaru.This type of research can be classified in type of sociological research (empirical), because in this study the author directly conducts research on the locations or the places that are researched in order to give a complete and clear overview of the issues that areresearched. This research was conducted in the Pekanbaru City Police, while the population and the sample are all of the part that related withthis research, the data source is used, among others, the primary data, the secondary data, and the tertiary data, data collection techniques interview and literature. From the research, there are three fundamental problems that can be concluded.First, diversionary application in Pekanbaru City Police has been implemented according to procedures of an applicable law, it is just not running properly like is regulated in Law.Second, barriers which are faced Pekanbaru City Police in implementing diversion in cases of children in a conflict with the law, among others,factor of an identity, factor of a child psychology, awareness of law of citizens factor,law enforcement officials factor such as increasing knowledge and increasing thequality of investigators children.Thesuggestions, First,Enacting and implementing diversion in accordance with the Law.Second, adding children investigators especially woman investigator. Third, Creating a special room special examinations of children and child custody.Keywords: Implementing – Diversion – Children